Genetic variation of soybean collection based on microsatellite DNA markers related to plant height - Podzorova, T.; Zatybekov, A.; Didorenko, S.; Abugalieva, S. (Eurasian Journal of Applied Biotechnology, 2022)
Soybean is a relatively new crop in Kazakhstan, and the development of new competitive cultivars with high productivity and quality is an important direction in the local breeding program. Previously, one of the major approaches for the development of new cultivars was breeding projects based on the evaluation of key morphological traits, including flowering time and plant height (PH). However, with the development of soybean genetics new molecular tools have emerged, including the development of DNA microsatellites, or simple sequence repeats (SSRs). In this study, a collection of hundred accessions grown in the southeast of Kazakhstan in 2020-2021 was assessed using eight agronomic traits, including plant height (PH), the height of lowest pod, number of lateral branches, number of fertile nodes, number of seeds per plant, thousand seeds weight, yield per square meter (YP2), and maturity group. The assessment of field trials showed a wide range of variability in agronomic traits and suggested that PH is significantly correlated with all studied traits, including YP2. The collection was genotyped using eight SSRs associated with PH. The results suggested that three SSRs (Satt244, Satt288, and Satt371) were the most polymorphic, and five out of eight SSRs were associated with six important agronomic traits, including flowering time, PH, and yield per square meters. Obtained results can be efficiently used in soybean breeding based on a marker-assisted selection approach.